The March of Time: The Cold War 1946-1951, Part 2: Hostility Grows 1948-1949 (United States, 1995)
Originally produced as a newsreel by Time Magazine, The March of Time was seen monthly for sixteen years in more than 50,000 theatres around the world. 1. Battle for Germany -- A must for updating oneself on the developments in Germany. There is no war guilt shown by the activities in the daily life of a typical family. Democratic ways come hard to this Teutonic race, and we see the communists sabotage the U.S. program by inciting labor unrest, as well as the "Airlift Crisis." 2. America's New Air Power -- The race for superior technology is on! Already the planes that won the war are obsolete. In this fascinating film we see the swing to jet propulsion, the incredible size of these planes and a new breed of specially trained "jet" pilots. 3. Answer to Stalin -- Did we defeat the Nazis just to trade them for the communists? Concern for Russian tactics in world politics is growing. Communist success in creating strife in Middle Europe is highlighted, plus the current tension in France and Germany. The film climaxes with a view of the Economic Cooperation Administration under Paul Hoffman. 4. Asia's New Voice -- The dramatic, inspiring birth of a nation--India! A country of extremes, it has fabulously wealthy princes and dirt-poor "Untouchables." With its own mysterious caste system and its terror stricken migrations, India is a Twentieth Century phenomenon. An impartial view of the weakness and strengths of this new, potentially great, nation is the focus of this study. 5. Report on the Atom -- What exactly is Atomic Power, and how is it going to affect us? These are the issues dealt with in this relevant study. The production of radioactive materials and the disposal of the dangerous waste combine with a look at the use of these materials in industry, agricultural and medical research.